Propofol Sedation in Diagnostic Upper Gastrointestinal Endoscopy - Christophorus Simadibrata; Benvenuto Axel; Syahrizal Syahrizal; Dina Ikawari; Paulus Simadibrata; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Sedation are commonly used these days in patients that having gastrointestinal endoscopy. Propofol is sedative  agent  that  commonly  used  in  endoscopy procedure.Method: All   patients   who   were   performed   diagnostic   EGD   in   Abdi   Waluyo   Hospital’s Gastrointestinal Endoscopy Unit from January 1st   2017 – 31st   December 2017, included in this study. The amount of Propofol, duration during hypnosis/sedation and adverse effects were all recorded.Results: 170  patients  were  performed  diagnostic  EGD  with  Propofol  sedation,  most  of them were male (87 patients, 51,5%). The median age was 48,78 + 14. The median Body Mass Index  (BMI)  was  24.45.  The median of duration of hynosis (sedation) during EGD was 5 minutes. The median of propofol total dose during EGD was 180 mg. Adverse effects that found during Propofol sedation are muscle twitching(10.6% patients) and pain in area of  injection(80% patients). Conclusion: The duration of propofol hypnosis/sedation during Esophagogastroduodenoscopy examination was 5 minutes. Propofol total dose needed for diagnostic EGD was 180 mg. The common adverse effects of propofol are muscle twitching and pain in area of injection.